2017
DOI: 10.1111/add.13940
|View full text |Cite
|
Sign up to set email alerts
|

Setting research priorities in tobacco control: a stakeholder engagement project

Abstract: Background and AimsThe Cochrane Tobacco Addiction Group (TAG) conducts systematic reviews of the evidence for tobacco cessation and prevention interventions. In 2016 TAG conducted a priority‐setting, stakeholder engagement project to identify where further research is needed in the areas of tobacco control and smoking cessation.DesignThe project comprised two surveys and a workshop. A range of stakeholders participated, including members of the public (smokers and ex‐smokers), clinicians, researchers, research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 6 publications
0
30
0
2
Order By: Relevance
“…However, this is not uncommon in multi-round prioritisation projects. [7,12] Nevertheless, the 53% response rate in round 2, is 10% lower than response rates in similar two-round survey prioritisation exercises conducted by other Cochrane groups [5,7] and may have exaggerated the biases noted above.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this is not uncommon in multi-round prioritisation projects. [7,12] Nevertheless, the 53% response rate in round 2, is 10% lower than response rates in similar two-round survey prioritisation exercises conducted by other Cochrane groups [5,7] and may have exaggerated the biases noted above.…”
Section: Discussionmentioning
confidence: 99%
“…Prioritisation projects relying solely on respondents to write-in their proposed topics have been conducted, [7] or are currently in progress, [14] however, this approach has previously been found to yield a very large number of unanswerable questions. For example, a similar exercise by the Cochrane Tobacco Addiction Group found that of the 258 questions suggested by the respondents, 183 (or 71%) were unanswerable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15] Submitted questions were screened by at least two reviewers (NED, VMS, CJB, AJP) to remove duplicates and any that fell outside the scope of the study. The remaining questions were rephrased for clarity and consistency of terminology, as required, and classified according to the current literature as: unanswered by current research; already answered by published research; or unable to be answered by scientific research.…”
Section: Methodsmentioning
confidence: 99%